Hak Atas Kesehatan Seksual Reproduksi bagi Perempuan: Kajian Perbandingan Mengenai Pengaturan Tentang Aborsi di Nepal dan Indonesia - Yogi Paramitha Dewi (Jurnal Perempuan, 2023)
The fulfillment of women’s sexual and reproductive health and rights remains challenging, especially concerning one of its most controversial issues, namely abortion. While the maternal deaths caused by unsafe abortion continue to be a concern, many countries retain repressive laws by banning abortion which has often been influenced by moral and religious reasons. This article aims to examine the abortion legal framework as part of sexual and reproductive health and rights through the lens of z by dissecting the degree of recognition of bodily integrity, personhood, equality, and diversity of women. Through a comparative approach between Indonesia and Nepal, this paper argues that Nepal’s abortion regulation has a stronger recognition of women’s bodily integrity, personhood, equality, and diversity in its abortion legal framework compared to Indonesia. Therefore, Nepal’s experience in regulating abortion can serve as an inspiration for Indonesia in ensuring women’s sexual and reproductive health and rights